Research on Technical Improvement of HXD2 Eight-axle Freight Electric Locomotive - Suming YAO; Wen WANG; Minghui HUANG (机车电传动)
In order to meet the development needs of China's railway transportation, the technical improvement of HXD2 eight-axle freight electric locomotive was mainly based on independent design, and re-innovative design was carried out on the basis of the development and application of existing HXD2 electric locomotive. Relying on the latest technical achievements in locomotive standard system and simplification in recent years, general technical improvements were made on the locomotive in terms of heavy load adaptability, simplification and interconnection, reliability, technical upgrade and adaptability to the reform of repair schedule and repair system, so as to further optimized the performance of HXD2 eight-axle freight electric locomotive. Through the implementation of the project, the technical improvement of eight-axle freight electric locomotive was realized, and the existing technology upgrade and localization improvement of AC drive locomotive were realized too.